Effect of VPAC1 Blockade on Adipose Tissue Formation and Composition in Mouse Models of Nutritionally Induced Obesity - H. Roger Lijnen; Kathleen Freson; Marc F. Hoylaerts (Journal of Obesity)
Background. The pituitary adenylate cyclase activating polypeptide (PACAP) may affect adipogenesis and adipose tissue formation through interaction with its G-protein-coupled receptor VPAC1. Methods. We have used a monoclonal antibody (MAb 23A11) blocking VPAC1 in mouse models of nutritionally induced obesity. Results. Administration of MAb 23A11 (25 mg/kg body weight i.p. twice weekly) to 5-week old male C57Bl/6 mice kept on a high-fat diet for 15 weeks had no significant effect on weight gain, nor on subcutaneous (SC) or gonadal (GON) adipose tissue mass, as compared to the control MAb 1C8. However, adipocyte hypertrophy was observed in SC adipose tissue of MAb 23A11 treated mice. In a second study, 24 weeks old obese mice were treated for 5 weeks with MAb 23A11, without effect on body weight or fat mass, as compared to treatment with MAb 1C8. In addition, MAb 23A11 had no significant effect on glucose tolerance or insulin resistance in lean or obese C57Bl/6 mice. Conclusion. Blocking VPAC1 does not significantly affect adipose tissue formation in mouse models of diet-induced obesity, although it may be associated with mild adipocyte hypertrophy.